Molecular nutrition in life course perspective: Pinpointing metabolic pathways to target during periconception - Sergej M. Ostojic; Laszlo Ratgeber; Jozsef Betlehem; Pongrac Acs (Wiley, 2024)
Abstract Lifecourse nutrition encompasses nourishment from early development into parenthood. From preconception and pregnancy to childhood, late adolescence, and reproductive years, life course nutrition explores links between dietary exposures and health outcomes in current and future generations from a public health perspective, usually addressing lifestyle behaviours, reproductive well‐being and maternal‐child health strategies. However, nutritional factors that play a role in conceiving and sustaining new life might also require a molecular perspective and recognition of critical interactions between specific nutrients and relevant biochemical pathways. The present perspective summarises evidence about the links between diet during periconception and next‐generation health and outlines the main metabolic networks involved in nutritional biology of this sensitive time frame.